Crosslinkable fluororesin composition, molded article, crosslinked molded article, and coated electric wire
By using the cross -linked auxiliary agent and phenolic and phosphoric antioxidants that include multi -unsaturated alkali and phenolic and phosphorus atomic antioxidants to solve the problems of ETFE formats and cross -linking forms in terms of heat resistance and coloring The formation of excellent thermal resistance and colorless formation and overwriting.
Patent Information
- Application Number
- CN202380046790.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-20
- Filing Date
- 2023-06-09
- Publication Date
- 2025-01-24
AI Technical Summary
The existing ETFE molded bodies or crosslinked molded bodies have insufficient heat resistance and are prone to coloring problems.
A crosslinkable fluororesin composition containing an ethylene- and tetrafluoroethylene-based fluororesin, a crosslinking assistant for polyunsaturated carbon bonds, and an antioxidant of at least one of a phenolic group and a phosphorus atom is used. The fluororesin of the composition has a melting point above 210°C, the cross-linking assistant improves the cross-linking efficiency, and the antioxidant enhances the thermal stability and antioxidant properties.
The forming body, cross -linking form and overwriting of the combined wires with excellent heat resistance and coloring problems are achieved, which improves the thermal stability and mechanical properties of the material.
Smart Images

Figure BDA0005185065630000181
Abstract
Description
Technical Field
[0001] The present invention relates to a cross-linkable fluororesin composition, a molded article, a cross-linked molded article and a coated electric wire. Background Art
[0002] The copolymer containing ethylene-based units and tetrafluoroethylene-based units (hereinafter also referred to as "ETFE") is excellent in heat resistance, weather resistance, electrical insulation, non-adhesiveness, water and oil repellency, etc. In addition, ETFE also has the characteristics of high moldability and mechanical strength among fluororesins.
[0003] Therefore, ETFE can be processed through melt molding methods such as extrusion molding, blow molding, injection molding, and rotational molding to produce a wide range of molded products such as coated wires, tubes, sheets, films, filaments, pump housings, connectors, packaging, linings, coatings, etc.
[0004] In some cases, a molded body of a resin composition obtained by blending a crosslinking aid in ETFE is irradiated with ionizing radiation to form a crosslinked molded body (Patent Document 1). Forming a crosslinked molded body can improve wear resistance and rigidity. However, the molded body or cross-linked molded body of ETFE does not necessarily have sufficient heat resistance. In addition, the molded body or cross-linked molded body also has the problem of coloration. Patent Document 2 discloses that copper oxide is blended into ETFE to improve the heat resistance of a molded body or a cross-linked molded body, but it is difficult to say that the effect is sufficient. Prior art literature Patent Literature
[0005] Patent Document 1: International Publication No. 2016 / 210314 Patent Document 2: International Publication No. 2013 / 015202 Summary of the invention Technical problem to be solved by the invention
[0006] The present invention provides a cross-linkable fluororesin composition which can provide a molded article, a cross-linked molded article and a coated electric wire which are excellent in heat resistance and are not prone to coloration. Technical solutions adopted to solve technical problems
[0007] The present invention has the following technical contents. [1] A cross-linkable fluororesin composition comprising: Fluorine resins containing ethylene-based units and tetrafluoroethylene-based units, capable of melt forming and having a melting point of 210°C or above; A crosslinking aid having multiple unsaturated carbon bonds; and An antioxidant having at least one of a phenolic group and a phosphorus atom and having a molecular weight of 600 or more. [2] The cross-linkable fluororesin composition according to [1], wherein the antioxidant has a phenol group and a phosphorus atom. [3] The cross-linkable fluororesin composition according to [1] or [2], wherein the fluororesin further contains units derived from a monomer other than ethylene and tetrafluoroethylene. [4] The cross-linkable fluororesin composition according to any one of [1] to [3], wherein the fluororesin has a hydroxyl group at a main chain terminal. [5] A shaped body, The molded body is composed of a molding material containing a cross-linkable fluororesin composition. The cross-linkable fluororesin composition comprises: Fluorine resins containing ethylene-based units and tetrafluoroethylene-based units, capable of melt forming and having a melting point of 210°C or above; A crosslinking aid having multiple unsaturated carbon bonds; and An antioxidant having at least one of a phenolic group and a phosphorus atom and having a molecular weight of 600 or more. [6] The formed article according to [5], wherein the antioxidant has a phenol group and a phosphorus atom. [7] The molded article according to [5] or [6], wherein the fluororesin further contains units based on a monomer other than ethylene and tetrafluoroethylene. [8] The molded article according to any one of [5] to [7], wherein the fluororesin has a hydroxyl group at a main chain terminal. [9] A cross-linked shaped article, The cross-linked molded product is a cross-linked product of a molding material comprising a cross-linkable fluororesin composition. The cross-linkable fluororesin composition comprises: Fluorine resins containing ethylene-based units and tetrafluoroethylene-based units, capable of melt forming and having a melting point of 210°C or above; A crosslinking aid having multiple unsaturated carbon bonds; and An antioxidant having at least one of a phenolic group and a phosphorus atom and having a molecular weight of 600 or more.
[10] The cross-linked shaped article according to [9], wherein the antioxidant has a phenol group and a phosphorus atom.
[11] The cross-linked shaped article according to [9] or
[10] , wherein the fluororesin further contains units based on a monomer other than ethylene and tetrafluoroethylene.
[12] The cross-linked shaped article according to any one of [9] to
[11] , wherein the fluororesin has a hydroxyl group at a main chain terminal.
[13] A covered electric wire comprising a covering layer, wherein the covering layer is the cross-linked shaped article according to any one of [9] to
[12] . Effects of the Invention
[0008] According to the cross-linkable fluororesin composition of the present invention, it is possible to obtain a molded article, a cross-linked molded article, and a covered electric wire which are excellent in heat resistance and are less likely to cause coloration problems. The molded article, cross-linked molded article and covered electric wire of the present invention are excellent in heat resistance and are unlikely to cause coloration problems. DETAILED DESCRIPTION
[0009] <Terms> The term "unit" refers to a general term for an atomic group directly formed by polymerizing one molecule of a monomer and an atomic group obtained by chemically converting a part of the atomic group. The "monomer-based unit" refers to an atomic group formed directly by polymerization of a monomer 1 molecule. "Monomer" refers to a compound having a polymerizable carbon-carbon double bond.
[0010] "Melt-formable" means exhibiting melt fluidity. A "crosslinked shaped body" is a shaped body which no longer exhibits melt fluidity. “Exhibiting melt fluidity” means that under a load of 49 N, there is a temperature at which the melt flow rate reaches 0.1 to 1000 g / 10 minutes at a temperature 20° C. or higher than the melting point of the resin. The “melt flow rate” refers to the melt flow rate (MFR) specified in JIS K 7210-1:2014 (corresponding to the international standard ISO 1133-1:2011). The "melting point" refers to the temperature corresponding to the maximum of the melting peak measured by differential scanning calorimetry (DSC).
[0011] The "crosslinking auxiliary agent" refers to an admixture required at a low concentration to increase the crosslinking efficiency when a polymer undergoes a crosslinking reaction and forms a crosslinked polymer. The term "antioxidant" refers to an additive added for the purpose of preventing deterioration, discoloration, or deterioration due to oxidation. The "mass average molecular weight" of a fluororesin is an average molecular weight obtained by taking into account the mass fraction characterized by the GPC method.
[0012] The “tensile strength” and “tensile elongation” are obtained by preparing ASTM D Type V dumbbell-shaped test pieces (thickness 1 mm) from the sample (fluororesin composition or fluororesin) and subjecting the test pieces to a tensile test under the conditions of ASTM D 638. " to " indicating a numerical range means a range including the numerical values described before and after it as the lower limit and the upper limit. The lower limit and the upper limit of the numerical range disclosed in this specification can be combined arbitrarily to generate a new numerical range.
[0013] <Crosslinkable fluororesin composition> The crosslinkable fluororesin composition of the present invention comprises: a fluororesin containing ethylene-based units and tetrafluoroethylene-based units, capable of melt molding and having a melting point of 210° C. or higher; a crosslinking aid having multiple unsaturated carbon bonds; and an antioxidant having at least one of a phenolic group and a phosphorus atom and having a molecular weight of 600 or higher.
[0014] [Fluororesin] The fluororesin in the fluororesin composition is a copolymer (ETFE) containing units based on ethylene (hereinafter also referred to as "E") (hereinafter also referred to as "E units") and units based on tetrafluoroethylene (hereinafter also referred to as "TFE") (hereinafter also referred to as "TFE units").
[0015] As ETFE, a copolymer containing E units, TFE units, and units based on monomers other than ethylene and TFE (hereinafter also referred to as "other monomer units") is preferred from the viewpoint of having better heat resistance, mechanical properties, and chemical resistance. Any other monomer may be used as long as it is copolymerizable with ethylene and TFE, and one kind may be used alone or two or more kinds may be used in combination.
[0016] Examples of other monomer units include units based on the following monomers (1) to (7). The following monomers (1) to (7) may be used alone or in combination of two or more. (1) A compound represented by the following formula 1. CH 2 =CX(CF 2 ) n Z-style 1 Here, X and Z are each independently a hydrogen atom or a fluorine atom, and n is an integer of 1-10. (2) Olefins such as propylene, butene, isobutylene, etc. (but excluding ethylene). (3) Fluoroolefins whose unsaturated groups do not have hydrogen atoms, such as hexafluoropropylene (HFP) and chlorotrifluoroethylene (CTFE) (except TFE). (4) Fluoroolefins having a hydrogen atom in the unsaturated group, such as vinylidene fluoride (VDF), vinyl fluoride (VF), trifluoroethylene, and hexafluoroisobutylene (HFIB). (5) Perfluoro(alkyl vinyl ether) (PAVE) such as perfluoro(methyl vinyl ether) (PMVE), perfluoro(ethyl vinyl ether) (PEVE), perfluoro(propyl vinyl ether) (PPVE), and perfluoro(butyl vinyl ether) (PBVE). (6)CF 2 =CFOCF 2 CF=CF 2 CF 2=CFO(CF 2 ) 2 CF=CF 2 Such as perfluorovinyl ether having two unsaturated bonds. (7) Fluorine-containing monomers having an alicyclic structure, such as perfluoro(2,2-dimethyl-1,3-dioxole) (PDD), 2,2,4-trifluoro-5-trifluoromethoxy-1,3-dioxole, and perfluoro(2-methylene-4-methyl-1,3-dioxane).
[0017] Among them, from the viewpoint of better mechanical properties and thermal stability, it is preferred to include a unit based on the compound represented by the above formula 1 (hereinafter also referred to as "FAE"). X in Formula 1 is preferably a hydrogen atom from the viewpoint of superior flexibility, elongation and strength. In Formula 1, Z is preferably a fluorine atom from the viewpoint of better heat resistance and chemical resistance. In Formula 1, n is preferably 2 to 8, more preferably 2 to 6, and further preferably 2, 4 or 6. When n is at least the lower limit, the mechanical properties and thermal stability of the present composition are further improved, and when it is at most the upper limit, FAE has sufficient polymerization reactivity.
[0018] As a preferred example of FAE, CH 2 =CH(CF 2 ) 2 F, CH 2 =CH(CF 2 ) 4 F, CH 2 =CH(CF 2 ) 6 F, CH 2 =CF(CF 2 ) 4 F, CH 2 =CF(CF 2 ) 3 Among them, CH is preferred from the perspective of better mechanical properties and thermal stability. 2 =CH(CF 2 ) 4 F (hereinafter also referred to as PFBE). FAE may be used alone or in combination of two or more.
[0019] In ETFE, the molar ratio of E unit to TFE unit (E unit / TFE unit) is preferably 30 / 70 to 60 / 40, more preferably 35 / 65 to 60 / 40. If the E unit / TFE unit is above the lower limit, the melting point of ETFE is sufficiently high, and the heat resistance and rigidity at high temperature are excellent. If it is below the upper limit, the chemical resistance is excellent.
[0020] The ratio of other monomer units is preferably 0.7 to 5.0 mol%, more preferably 0.9 to 4.0 mol%, relative to all units constituting ETFE. If the ratio of other monomer units is above the lower limit, stress crack resistance at high temperatures is more excellent, and if it is below the upper limit, the melting point of ETFE is sufficiently high, and heat resistance and rigidity at high temperatures are excellent.
[0021] ETFE preferably has a hydroxyl group at the main chain terminal. Fluororesin containing ETFE having a hydroxyl group at the main chain terminal as a main component improves heat resistance and easily improves the tensile strength retention rate and tensile elongation retention rate described below. The main chain ends of ETFE can be determined by analyzing ETFE using infrared spectroscopy.
[0022] The hydroxyl content at the end of the main chain is the hydroxyl peak (e.g. 3540 cm -1 The peak of the CF bond (e.g. 2210 cm -1 The area ratio of the peak of the main chain is preferably 1 to 50%, more preferably 3 to 30%. If the hydroxyl content at the main chain terminal is above the lower limit, the strength is excellent, and if it is below the upper limit, the heat resistance is more excellent. The hydroxyl content at the end of the main chain can be adjusted by the molecular weight of ETFE.
[0023] The fluororesin (ETFE) in the fluororesin composition can be melt-molded, that is, under a load of 49N, at a temperature 20°C higher than the melting point of the resin, at a temperature at which the melt flow rate (MFR) specified in JIS K 7210:1999 (ISO 1133:1997) reaches 0.1 to 1000 g / 10 minutes.
[0024] The melting point of the fluororesin (ETFE) in the fluororesin composition is 210° C. or higher. The melting point of the fluororesin is preferably 210 to 320° C., more preferably 245 to 270° C., and further preferably 250 to 265° C. When the melting point of ETFE is above the lower limit, heat resistance and rigidity at high temperatures are excellent, and when it is below the upper limit, moldability is excellent.
[0025] The melting point of the fluororesin (ETFE) can be adjusted by the molar ratio of the E unit to the TFE unit, the ratio of other monomer units to the total units constituting ETFE, and the like. In order to improve the melting point of ETFE, it is believed that, for example, the crystallinity can be improved by making the molar ratio of (E / TFE) close to 50 / 50 and reducing the content of other monomers. In addition, in order to reduce the melting point, it is believed that, for example, the crystallinity can be reduced by increasing the content of TFE so that the molar ratio of (E / TFE) is away from 50 / 50 and increasing the content of other monomers.
[0026] The melt flow rate (MFR) of the fluororesin (ETFE) at 297° C. is preferably 15 to 150 g / 10 min, more preferably 20 to 100 g / 10 min, further preferably 20 to 70 g / 10 min, particularly preferably 20 to 60 g / 10 min. The melt flow rate is also an indicator of molecular weight. The smaller the melt flow rate, the higher the molecular weight, and the larger the melt flow rate, the lower the molecular weight. If the melt flow rate at 297°C is 15 g / 10 minutes or more, it is advantageous for high-speed forming. If the melt flow rate at 297°C is 150 g / 10 minutes or less, the stress cracking resistance of the molded body is improved. If the melt flow rate at 297°C is within the numerical range, high-speed forming is excellent and stress cracking resistance is also excellent.
[0027] The melt flow rate of fluororesin (ETFE) can be controlled by adjusting the molecular weight of ETFE. For example, by adjusting the mass average molecular weight of ETFE to about 300,000 to about 600,000, the melt flow rate of ETFE at 297°C can be 15 to 150 g / 10 minutes.
[0028] The method for producing fluororesin (ETFE) is not particularly limited, and a polymerization method using a conventional free radical polymerization initiator can be adopted. Examples of the polymerization method include bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization. Solution polymerization is particularly preferred. As the radical polymerization initiator used for the polymerization, a radical chain initiator having a half-life of 10 hours at a temperature of 0 to 100°C is preferred, and a radical chain initiator having a half-life of 20 to 90°C is more preferred.
[0029] Examples of the free radical chain initiator include: azo compounds such as azobisisobutyronitrile; peroxydicarbonates such as diisopropyl peroxydicarbonate; peroxyesters such as tert-butyl peroxypivalate, tert-butyl peroxyisobutyrate, and tert-butyl peroxyacetate; non-fluorinated diacyl peroxides such as isobutyryl peroxide, octanoyl peroxide, benzoyl peroxide, and lauroyl peroxide; (Z(CF 2 ) p COO 2 (herein, Z is a hydrogen atom, a fluorine atom or a chlorine atom, and p is an integer of 1 to 10) and the like; perfluoro tert-butyl peroxide; inorganic peroxides such as potassium persulfate, sodium persulfate, and ammonium persulfate.
[0030] When the fluororesin (ETFE) is produced by solution polymerization, examples of the polymerization medium include organic solvents such as fluorocarbons, chlorocarbons, fluorochlorocarbons, alcohols, and hydrocarbons. Examples of the polymerization medium include perfluorocarbons such as n-perfluorohexane, n-perfluoroheptane, n-perfluorocyclobutane, perfluorocyclohexane, and perfluorobenzene; 1,1,2,2-tetrafluorocyclobutane, CF 3 CFHCF 2 CF 2 CF 3 CF 3 (CF 2 ) 4 H.CF 3 CF 2 CFHCF 2 CF 3 CF 3 CFHCFHCF 2 CF 3 CF 2 HCFHCF 2 CF 2 CF 3 CF 3 (CF 2 ) 5 H.CF 3 CH(CF 3 )CF 2 CF 2 CF 3 CF 3 CF(CF 3 )CFHCF 2 CF 3 CF 3 CF(CF 3 )CFHCFHCF 3 CF 3 CH(CF 3 )CFHCF 2 CF 3 CF 3 CF 2 CH 2 CH 3 CF 3 (CF 2 ) 3 CH 2 CH 3 Hydrofluorocarbons; CF 3 CH 2 OCF 2 CF 2 H.CF 3 (CF 3 )CFCF 2OCH 3 CF 3 (CF 2 ) 3 OCH 3 Hydrofluoroether, etc.
[0031] The polymerization conditions are not particularly limited. The polymerization temperature is preferably 0 to 100° C., more preferably 20 to 90° C. The polymerization pressure is preferably 0.1 to 10 MPa, more preferably 0.5 to 3 MPa. The polymerization time is preferably 1 to 30 hours. The method for regulating the molecular weight of ETFE, i.e., the method for regulating the melt flow rate of ETFE, is not particularly limited. For example, methods for regulating the molecular weight during polymerization such as the addition of a chain transfer agent and the control of polymerization pressure, methods for regulating the molecular weight by applying energy such as heat or radiation to the ETFE obtained by polymerization to cut off the molecules, methods for regulating the molecular weight by chemically cutting off the molecular chains of the ETFE obtained by polymerization by free radicals, etc. are particularly preferred. The method of controlling the molecular weight during polymerization using a chain transfer agent is particularly preferred.
[0032] Examples of the chain transfer agent include alcohols such as methanol, ethanol, 2,2,2-trifluoroethanol, 2,2,3,3-tetrafluoropropanol, 1,1,1,3,3,3-hexafluoroisopropanol, and 2,2,3,3,3-pentafluoropropanol; fluorochlorocarbons such as 1,3-dichloro-1,1,2,2,3-pentafluoropropane and 1,1-dichloro-1-fluoroethane; hydrocarbons such as n-pentane, n-hexane, n-heptane, and cyclohexane; and CF 2 H 2 Hydrofluorocarbons such as acetone; ketones such as acetone; thiols such as methyl mercaptan; esters such as methyl acetate and ethyl acetate; ethers such as ethyl ether and methyl ethyl ether, etc. The amount of chain transfer agent added is about 0.01 to 100 mass % relative to the conventional polymerization medium. By adjusting the amount of chain transfer agent added, the melt viscosity (molecular weight) of the obtained ETFE can be adjusted. That is, the higher the amount of chain transfer agent added, the lower the molecular weight of ETFE can be obtained.
[0033] Fluororesin (ETFE) having hydroxyl groups at the ends of the main chains can be obtained, for example, by using alcohol as a chain transfer agent when polymerizing monomers. For example, paragraph
[0016] of Japanese Patent Publication No. 2016-043566 states that, when alcohol is used as a chain transfer agent, alcoholic hydroxyl groups are introduced into the ends of the main chains of ETFE to obtain ETFE having an end group consisting of hydroxyl groups at the ends of the main chains.
[0034] The fluororesin (ETFE) in the fluororesin composition may be a commercially available product or a product produced by various methods. For example, it can be produced by the method described in paragraphs
[0021] to
[0025] of Patent Document 1 or the method described in paragraphs
[0036] to
[0043] of International Publication No. 2016 / 006644.
[0035] [Crosslinking aid] The crosslinking aid in the fluororesin composition has two or more unsaturated bonds in one molecule. Examples of the crosslinking aid include triallyl cyanurate, triallyl isocyanurate, bismaleimide, ethylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, trimethylolpropane trimethacrylate, and divinylbenzene. Among them, triallyl isocyanurate called TAIC is preferred because of its high thermal stability.
[0036] The crosslinking aid is preferably blended in an amount of 0.5 to 20 parts by mass, preferably 2 to 8 parts by mass, relative to 100 parts by mass of the fluororesin. If the blending amount of the crosslinking aid is above the preferred lower limit, the strength is excellent. If the blending amount of the crosslinking aid is below the preferred upper limit, the elongation is excellent.
[0037] [Antioxidant] The antioxidant in the fluororesin composition has at least one of a phenol group and a phosphorus atom and has a molecular weight of 600 or more. The antioxidant preferably has both a phenolic group and a phosphorus atom. Preferred examples of antioxidants are listed below, and two or more kinds thereof may be selected and used in any combination.
[0038] Examples of the antioxidant having both a phenol group and a phosphorus atom include 2-tert-butyl-6-methyl-4-[3-(2,4,8,10-tetra-tert-butylbenzo[d][1,3,2]benzodioxaphosphin-6-yl)oxypropyl]phenol and phosphorus-modified novolac-type phenol resins. Among them, 2-tert-butyl-6-methyl-4-[3-(2,4,8,10-tetra-tert-butylbenzo[d][1,3,2]benzodioxaphosphin-6-yl)oxypropyl]phenol is preferred because of its excellent thermal stability.
[0039] Examples of the antioxidant having a phenol group include bisphenol A, bisphenol AF, phenol, cresol, p-phenylphenol, m-phenylphenol, o-phenylphenol, allylphenol, p-hydroxybenzoic acid, ethyl p-hydroxybenzoate, and hindered phenols.
[0040] Examples of hindered phenols include octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, octyl 3-(4-hydroxy-3,5-diisopropylphenyl)propionate, and bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propanoate][2,2-bis[[1-oxo-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propoxy]methyl]propane]-1,3-diyl.
[0041] As the antioxidant having a phosphorus atom, a phosphorus compound having a trivalent phosphorus atom is preferred. The trivalent phosphorus atom exists in the molecule in the form of a phosphine group or a phosphonate group. The trivalent phosphorus atom oxidizes to a pentavalent state, which brings about a peroxide decomposition effect (eliminating the free radicals generated by the peroxide), thus having antioxidant properties.
[0042] Examples of the antioxidant having a trivalent phosphorus atom include trioctyl phosphite, trilauryl phosphite, tridecyl phosphite, (octyl) diphenyl phosphite, tris(2,4-di-tert-butylphenyl) phosphite, triphenyl phosphite, tris(butoxyethyl) phosphite, tris(nonylphenyl) phosphite, distearyl pentaerythritol diphosphite, tetra(tridecyl)-1,1,3-tris(2-methyl-5-tert-butyl-4-hydroxyphenyl)butane diphosphite, tetra(C 12 ~C 15 mixed alkyl)-4,4'-isopropylidene diphenyl diphosphite, tetra(tridecyl)-4,4'-butylene bis(3-methyl-6-tert-butylphenol) diphosphite, tris(3,5-di-tert-butyl-4-hydroxyphenyl) phosphite, tris(mono- and di-mixed nonylphenyl) phosphite, hydrogenated-4,4'-isopropylidene diphenol polyphosphite, bis(octylphenyl)bis[4,4'-butylene bis(3-methyl-6-tert-butylphenol)]-1,6-hexanediol diphosphite, phenyl(4,4'-isopropylidene diphenol) pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, tris[4,4'-isopropylidene bis(2-tert-butylphenol)] phosphite, di(isodecyl)phenyl phosphite, 4,4'-isopropylidene diphenol (2-tert-butylphenol)bis(nonylphenyl)phosphite, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, bis(2,4-di-tert-butyl-6-methylphenyl)ethylphosphite, 2-[{2,4,8,10-tetra-tert-butyldibenzo[d,f][1.3.2]-dioxaphosphin-6-yl}oxy]-N,N-bis[2-[{2,4,8,10-tetra-tert-butyldibenzo[d,f][1.3.2]-dioxaphosphin-6-yl}oxy]ethyl]ethanamine, 6-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-tert-butyldibenzo[d,f][1.3.2]-dioxaphosphine, bis(dialkylphenyl)pentaerythritol diphosphite.
[0043] As the antioxidant having a trivalent phosphorus atom, commercially available products can be used. Examples of commercially available products include Irgafos 168 (registered trademark, manufactured by Ciba Specialty Chemicals), Irgafos 12 (registered trademark, manufactured by Ciba Specialty Chemicals), Irgafos 38 (registered trademark, manufactured by Ciba Specialty Chemicals), ADEKA329K (registered trademark, manufactured by Asahi Denka Industries, Ltd.), ADEKA PEP36 (registered trademark, manufactured by Asahi Denka Industries, Ltd.), ADEKA PEP-8 (registered trademark, manufactured by Asahi Denka Industries, Ltd.), Sandstab P-EPQ (registered trademark, manufactured by Clariant), WESTON 618 (registered trademark, manufactured by GE), WESTON 619G (registered trademark, manufactured by GE), Ultranox 626 (registered trademark, manufactured by GE), and Sumilizer GP (registered trademark, manufactured by Sumitomo Chemical Co., Ltd.).
[0044] The molecular weight of the antioxidant in the fluororesin composition is at least 600. The molecular weight of the antioxidant is preferably 600 to 50,000, more preferably 600 to 3,000. The antioxidant has excellent thermal stability when the molecular weight is 600 or more. When the molecular weight of the antioxidant is below the preferred upper limit, the antioxidant has excellent dispersibility in other polymer components.
[0045] The antioxidant is preferably blended in an amount of 0.001 to 20 parts by mass, preferably 0.01 to 5 parts by mass, relative to 100 parts by mass of the fluororesin. If the blending amount of the antioxidant is above the preferred lower limit, the thermal stability is excellent. If the blending amount of the antioxidant is below the preferred upper limit, the mechanical properties are excellent.
[0046] [Other ingredients] The crosslinkable fluororesin composition of the present invention may further contain other components as necessary. The other components may be used alone or in combination of two or more. As other components, fillers, plasticizers, additives such as flame retardants, etc. can be mentioned. For example, the components described in paragraphs
[0042] to
[0048] of International Publication No. 2019-198771 can be mentioned.
[0047] In addition, fluororesins or fluorine-containing elastomers other than ETFE may be contained as other components. In any case, the content is preferably less than 50% by mass, more preferably less than 35% by mass, relative to ETFE.
[0048] Examples of fluororesins other than ETFE include TFE / HFP copolymers (copolymers containing TFE units and HFP units, the same applies hereinafter), TFE / HFP / PAVE copolymers, TFE / PAVE copolymers [PFA], E / TFE / HFP copolymers, polychlorotrifluoroethylene [PCTFE], CTFE / TFE copolymers, CTFE / TFE / PAVE copolymers, E / CTFE copolymers, TFE / VDF copolymers, VDF / HFP / TFE copolymers, VDF / HFP copolymers, polyvinylidene fluoride (PVDF), and polyvinyl fluoride (PVF).
[0049] Examples of the fluorine-containing elastomer include TFE / propylene (P) copolymers, HFP / VDF copolymers, and TFE / PAVE copolymers. Among them, TFE / P copolymer, HFP / VDF copolymer and TFE / PAVE copolymer which are fluorine-containing elastomers are preferred.
[0050] <Molded body> The molded article of the present invention is a molded article composed of a molding material containing the cross-linkable fluororesin composition of the present invention. The shape of the molded article of the present invention is not particularly limited and may be, for example, in the form of a ring, a film, a coating, or a block. The molded article of the present invention can be produced by molding the fluorinated copolymer composition of the present invention by various methods such as injection molding, extrusion molding, float molding, press molding, rotational molding, electrostatic coating, etc.
[0051] The fluorinated copolymer composition of the present invention has excellent fluidity at high temperatures and thus has excellent high-speed molding processability. In particular, in the case of injection molding, it has excellent melt fluidity and can be molded into even thin-walled and complex shapes. The shaped article of the present invention can be used to obtain the cross-linked shaped article of the present invention. In addition, the uncross-linked shaped article can be used, for example, for recycling or regeneration shaping.
[0052] <Cross-linked molded article> The cross-linked shaped article of the present invention is a cross-linked product of a molding material comprising the cross-linkable fluororesin composition of the present invention. The cross-linked shaped article of the present invention is obtained by cross-linking the shaped article of the present invention. For example, the cross-linked shaped article can be obtained by irradiating the shaped article with ionizing radiation such as gamma rays, electron rays, and X-rays. As the radiation, electron rays are preferred in terms of equipment.
[0053] The crosslinking conditions cannot be generalized because they are affected by the shape, thickness, etc. of the molded article, but it is preferably carried out at least once in an atmosphere with a temperature lower than the melting point of the fluororesin, preferably below the glass transition temperature, and at least once in an atmosphere with a temperature higher than the melting point of the fluororesin. By performing cross-linking by electron beam irradiation in an atmosphere at a temperature lower than the melting point of the fluororesin, the molded body will not melt or deform even if it is heated to a temperature higher than the melting point of the fluororesin during the second irradiation, and the shape of the molded body can be maintained. The dose of radiation is preferably 10-200 kGy, more preferably 30-100 kGy.
[0054] The tensile strength of the cross-linked shaped article is preferably 30 to 60 Pa, more preferably 35 to 60 Pa, and further preferably 40 to 60 Pa. When the tensile strength is at least the above lower limit, the rigidity is excellent, and when it is at most the above upper limit, the flexibility is excellent. The tensile elongation of the cross-linked shaped article is preferably 180 to 600%, more preferably 200 to 600%, and further preferably 250 to 600%. If the tensile elongation is at least the lower limit, the flexibility is excellent, and if it is at most the upper limit, the rigidity is excellent.
[0055] The tensile strength retention rate after the cross-linked shaped article is kept at 210° C. for 85 days is preferably 50% or more, more preferably 65% or more, and even more preferably 80% or more. The tensile elongation retention rate after the cross-linked shaped article is kept at 210°C for 85 days is preferably 60% or more, more preferably 90% or more, and even more preferably 150% or more. When each retention rate is more than the above lower limit, the thermal stability is excellent.
[0056] The cross-linked molded article can be used as a wide range of molded products such as coated wires, pipes, sheets, films, filaments, pump housings, joints, packaging, linings, coatings, etc. Among them, covered electric wires are preferred. The covered electric wire of the present invention has a covering layer, and the covering layer (insulating layer or sheath layer) is the crosslinked shaped article of the present invention. The crosslinked shaped article of the present invention is preferred as either the insulating layer or the sheath layer in the covered electric wire. Example
[0057] Hereinafter, the present invention will be described by way of examples, but the present invention is not limited to these examples. Examples 1 to 5 are examples, and Examples 6 to 10 are comparative examples.
[0058] <Raw materials> The raw materials used in each example are as follows. Fluororesin 1: Powdered ETFE, composed of TFE unit / E unit / CH 2 =CH(CF2 ) 4 F unit = 54 / 46 / 1.4 (molar ratio), melting point 260°C, average particle size 30 μm.
[0059] Crosslinking aid: Triallyl isocyanurate Antioxidant: 2-tert-butyl-6-methyl-4-[3-(2,4,8,10-tetra-tert-butylbenzo[d][1,3,2]benzodioxaphosphin-6-yl)oxypropyl]phenol (molecular weight 676.9) Copper Oxide: CuO
[0060] <Examples 1 to 3, 6, 7, 10> The fluororesin compositions shown in Table 1 were extruded by a twin-screw extruder ( The mixture was melt-kneaded using a twin-screw extruder manufactured by TECHNOVEL Co., Ltd. to obtain pellets. The kneading conditions were a barrel temperature of 280 to 300° C., a die temperature of 300° C., and a screw speed of 200 rpm. The obtained pellets were pressed at 300°C to prepare sheets with a thickness of 1 mm. The sheets were punched out with an ASTM D Type V dumbbell to prepare molded body samples.
[0061] <Examples 4, 5, 8, 9> The fluororesin compositions shown in Table 1 were extruded by a twin-screw extruder ( The mixture was melt-kneaded using a twin-screw extruder manufactured by Technovel Co., Ltd. to obtain pellets. The kneading conditions were a barrel temperature of 280 to 300°C, a die temperature of 300°C, and a screw speed of 200 rpm. The obtained pellets were pressed at 300°C to prepare sheets with a thickness of 1 mm. The sheets were punched out with an ASTM D Type V dumbbell to prepare molded body samples. Next, the obtained molded product samples were irradiated with electron beams at the doses shown in Table 1 to obtain cross-linked molded product samples.
[0062] <Tensile test> The molded body samples of each example (Examples 4, 5, 8, and 9 are cross-linked molded body samples, and the same applies below) were subjected to a tensile test at room temperature under the conditions of a tensile evaluation point spacing of 7.62 mm and a tensile speed of 200 mm / min to measure tensile strength and tensile elongation. The average values of the measured values obtained for the 5 molded body samples are shown in Table 1.
[0063] <Heat resistance test> After the molded body samples of each example (Examples 4, 5, 8, and 9 are cross-linked molded body samples, the same applies below) were kept in a gear oven at 210°C for a predetermined number of days (31 days or 85 days), the tensile test was performed to measure the tensile strength and tensile elongation. The average values of the measured values obtained for the 5 molded body samples are shown in Table 1. Table 1 shows the ratios (retention rates) of the obtained measured values to the measured values obtained for the molded body before heating in the gear oven.
[0064] <Evaluation of electric wire> The pellets obtained in each example were extruded into The core wire is formed into a coating layer with a wall thickness of 0.2 mm, and is made of (Tolerance: about ±0.01 mm) and 50 m long electric wire. In Examples 1 to 3, 6, 7, and 10, the electric wire was made into electric wire samples. In Examples 4, 5, 8, and 9, the electric wire was further irradiated with electron beams at the doses shown in Table 1 to make electric wire samples.
[0065] The wire extrusion conditions are single-axis extruder ( L / D=24), barrel temperature 280-320°C, die temperature 320°C, screw speed 30rpm, line speed 10m / min, cooling by water cooling. The obtained electric wire samples were visually observed and the number of black spots was counted. The results are shown in Table 1.
[0066] <Dripping resistance> The molded body sample of each example (Examples 4, 5, 8, and 9 are cross-linked molded body samples, and the same applies to the following) was crushed with a cutter to obtain a test powder with a major diameter of less than 2 mm. The MFR of the obtained test powder was determined in accordance with ASTM D3159 under the conditions of a temperature of 297° C. and a load of 49 N. From the results, the presence or absence of anti-drip properties was evaluated according to the following criteria.
[0067] Yes: MFR is less than 1.0 g / 10 minutes. None: MFR greater than 1.0 g / 10 min.
[0068] [Table 1]
[0069] As shown in Table 1, the molded articles (crosslinked molded articles) of Examples 1 to 5 had high retention rates of tensile strength and tensile elongation and showed high heat resistance. In addition, no black spots were observed in the wires of the molded articles (crosslinked molded articles) of Examples 1 to 5, and coloration was also confirmed to be suppressed. Possibility of industrial application
[0070] According to the cross-linkable fluororesin composition of the present invention, it is possible to obtain a molded article, a cross-linked molded article, and a covered electric wire which are excellent in heat resistance and are less likely to cause coloration problems. The molded article, cross-linked molded article and covered electric wire of the present invention are excellent in heat resistance and are unlikely to cause coloration problems.
[0071] This application claims priority based on Japanese Patent Application No. 2022-099070 filed with the Japan Patent Office on June 20, 2022, the entire contents of which are incorporated herein by reference.
Claims
1. A cross-linkable fluororesin composition comprising: Fluorine resins containing ethylene-based units and tetrafluoroethylene-based units, capable of melt forming and having a melting point of 210°C or above; A crosslinking aid having multiple unsaturated carbon bonds; and An antioxidant having at least one of a phenolic group and a phosphorus atom and having a molecular weight of 600 or more.
2. The cross-linkable fluororesin composition according to claim 1, wherein The antioxidant has a phenolic group and a phosphorus atom.
3. The cross-linkable fluororesin composition according to claim 1 or 2, wherein The fluororesin further contains units based on monomers other than ethylene and tetrafluoroethylene.
4. The cross-linkable fluororesin composition according to any one of claims 1 to 3, wherein The fluororesin has a hydroxyl group at the terminal of the main chain.
5. A shaped body, The molded body is composed of a molding material containing a cross-linkable fluororesin composition. The cross-linkable fluororesin composition comprises: Fluorine resins containing ethylene-based units and tetrafluoroethylene-based units, capable of melt forming and having a melting point of 210°C or above; A crosslinking aid having multiple unsaturated carbon bonds; and An antioxidant having at least one of a phenolic group and a phosphorus atom and having a molecular weight of 600 or more.
6. The formed body according to claim 5, wherein The antioxidant has a phenolic group and a phosphorus atom.
7. The molded article according to claim 5 or 6, wherein The fluororesin further contains units based on monomers other than ethylene and tetrafluoroethylene.
8. The molded article according to any one of claims 5 to 8, wherein The fluororesin has a hydroxyl group at the terminal of the main chain.
9. A cross-linked shaped article, The cross-linked molded product is a cross-linked product of a molding material comprising a cross-linkable fluororesin composition. The cross-linkable fluororesin composition comprises: Fluorine resins containing ethylene-based units and tetrafluoroethylene-based units, capable of melt forming and having a melting point of 210°C or above; A crosslinking aid having multiple unsaturated carbon bonds; and An antioxidant having at least one of a phenolic group and a phosphorus atom and having a molecular weight of 600 or more.
10. The cross-linked shaped article according to claim 9, wherein The antioxidant has a phenolic group and a phosphorus atom.
11. The cross-linked shaped article according to claim 9 or 10, wherein The fluororesin further contains units based on monomers other than ethylene and tetrafluoroethylene.
12. The cross-linked shaped article according to any one of claims 9 to 11, wherein The fluororesin has a hydroxyl group at the terminal of the main chain.
13. A covered electric wire, The covered electric wire has a covering layer. The coating layer is the cross-linked shaped article according to any one of claims 9 to 12.
Citation Information
Patent Citations
Laminate using ethylene / tetrafluoroethylene copolymer, article including the laminate and method for producing the laminate
JP2016043566A
Propulsion system for aircraft
JP2022099070A
Fluorine-containing copolymer composition
WO2013015202A1
Fluorine-containing copolymer and layered body
WO2016006644A1
Radiation crosslinked fluoropolymer compositions containing low level of extractable fluorides
WO2016210314A1